An Integrated Model of Voice-User Interface Continuance Intention: The Gender Effect. Issue 15 (14th September 2019) - Nguyen, Quynh N.; Ta, Anh; Prybutok, Victor
ABSTRACT: Advanced speech recognition technology facilitated the development of voice-based smart devices. Voice user interface (VUI) is now a common feature on smartphones, computers, smart home devices, and car systems. The fragmented and context focused literature on VUI motivates this examination of the relationship between perceived quality and customer satisfaction in VUI portable devices. This study is the first to introduce extrinsic motivational factors as an extension to Wixom and Todd's model. These additional antecedent factors add an enriched explanation of VUI user behavior. This study is also the first to consider the role of gender in a VUI behavior model. Our findings suggest that the proposed driving factors, including trust, perceived risks, perceived enjoyment, and mobile self-efficacy, significantly affect VUI user attitudes, which influence their continuance intention. Our results also address the role of gender on the association of attitude toward VUI use and its antecedents. The findings show that perceived risk (privacy concerns) and perceived ease of use are more influential on VUI use behavior of males than females. However, the effect of trust and mobile self-efficacy play a more crucial role for females than males.